Joan of Arc - Bull, Angela, 1936- (New York, N.Y. : Dorling Kindersley Pub., 2000)
A biography of the fifteenth-century peasant girl who led a French army to victory against the English, witnessed the crowning of King Charles VII, and was later burned at the stake for witchcraft.
Keywords: Joan, -- of Arc, Saint, -- 1412-1431 -- Juvenile literature; Joan, -- of Arc, Saint, -- 1412-1431 -- Pictorial works -- Juvenile literature; Joan, -- of Arc, Saint, -- 1412-1431.; Christian women saints -- France -- Biography -- Juvenile literature; Saints; Women -- Biography; France -- History -- Charles VII, 1422-1461 -- Pictorial works -- Juvenile literature; France -- History -- Charles VII, 1422-1461.